2006
DOI: 10.1002/mabi.200500236
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Heparin‐Loaded Microspheres: Carrier Molecular Composition and Microsphere Structure

Abstract: Microspheres of amphiphilic triblock polymers PLLA-PEG-PLLA were investigated as carriers for heparin delivery. Two series of PLLA-PEG-PLLA triblock were synthesized and prepared into microspheres with heparin loaded. The microspheres were hollow and the surface morphology varied from smooth to porous. The pore size increased with increasing PEG content. The microsphere size distribution showed that higher PEG content increased the average microsphere size. The release rate of heparin was closely related to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
(27 reference statements)
2
7
0
Order By: Relevance
“…7), in agreement with literature (Luo et al, 2006). Upon immersion in PBS, the membrane might be hydrated and swollen, thus the active ingredient heparin could diffuse through the opening pores out of the membrane.…”
Section: Discussionsupporting
confidence: 86%
“…7), in agreement with literature (Luo et al, 2006). Upon immersion in PBS, the membrane might be hydrated and swollen, thus the active ingredient heparin could diffuse through the opening pores out of the membrane.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, the curves also show that the T m of PLLA in the core‐shell fibers was at a range of 146–148°C which is remarkably lower than that in the single component fibers. This result can be ascribed to the fact that the molecular chains of polymer become smoother and easy to move by adding small molecule drug into electrospun fibers, a similar result can be found in the case of heparin‐loaded polymer microspheres 61…”
Section: Resultssupporting
confidence: 59%
“…This result can be ascribed to the fact that the molecular chains of polymer become smoother and easy to move by adding small molecule drug into electrospun fibers, a similar result can be found in the case of heparin-loaded polymer microspheres. 61 Figure 13 shows XRD patterns of the PLLA bulk resin and the various electrospun fibers. The asreceived PLLA exhibited two main diffraction peaks at 16.28 and 22.88 and a small peak at 24.88.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…Clinically, use of a HEP microcarrier will remarkably improve the bio-availability of HEP. Luo et al reported a kind of biodegradable HEP microcarrier with the EE of HEP less than 16.7% [28]. We recently described a HEP microcarrier prepared via layer-by layer self-assembly technique with 74.4% of EE [29].…”
Section: Discussionmentioning
confidence: 97%